(untitled) (Research, Society and Development, 2021)
Objective: The aim of this study was to estimate 5-year survival and the burden of cancer in a medium-sized city in Southern Brazil. Methods: A cohort study was performed using governmental data of incidence and mortality from cancer at Florianopolis/SC, Southern Brazil. Survival rates were performed using Kaplan Meier methods and log-rank test to compare curves. Disability-adjusted life years (DALY), years lived with disability (YLD) and years of life lost (YLL) and age-standardized rates of each indicator were estimated. Results: Thyroid, prostate and melanoma of skin had higher survival rates. Cancers presenting the highest burden, in decreasing order, were thyroid, prostate, breast, trachea, bronchus and lung, followed by colon and rectum. Conclusion: The estimates in local level could be help the health services to improve their quality. Highest burden was related to thyroid, prostate and breast due to the highest survival rates. Other cancer as trachea, bronchus and lung, and colon and rectum had high burden due to mortality.